Brief Communication: Featured Article: Histone H2A mono-ubiquitination and cellular transformation are inversely related in N-nitrosodiethylamine-induced hepatocellular carcinoma. Issue 16 (October 2016) - Bhattacharya, Saikat; Reddy, Divya; Ingle, Arvind; Khade, Bharat; Gupta, Sanjay
Aberrant changes in histone post-translational modifications are encountered frequently in diseases like cancer. Although histone H3 post-translational modifications have been extensively studied in context of diseases, the functionally important histone H2A PTM H2A119ub (H2Aub) has not gained much attention. In this study, we report that H2Aub markedly decreases in hepatocellular carcinoma. Usp21, a H2A deubiquitinase, is probably responsible for decrease in H2Aub. In addition, the H2Aub levels showed an inverse correlation with H3S10 phosphorylation (H3S10p) and the proliferative state of the cells. Downregulation of H2Aub is also associated with increased expression of growth factor gene lipocalin 2. Interestingly, we show that treatment of cells with histone deacetylase inhibitor trichostatin A results in increase of H2Aub and decrease in H3S10p. Our work for the first time suggests the in vivo association of H3S10p, H4ac, and H2A119ub with cellular transformation.